Clinical utility of blood tests in elite athletes with short term fatigue - Fallon, K. E. (British Journal of Sports Medicine, 2006)
Objective: To determine, in a population of elite athletes at their initial presentation with tiredness or fatigue, whether a set of haematological and biochemical investigations enhances the diagnostic process over and above the information gained from clinical history and examination.